The Relationship Between Family Support And Anxiety Levels In ACS (Acute Coronary Syndrome) Patients At Lavalette Hospital Malang - Yulinda Citra Noviana; Bayu Budi Laksono; Heny Nurmayunita (Akademi Keperawatan Yarsi Samarinda, 2026)
Acute Coronary Syndrome (ACS) is a cardiovascular emergency condition that can have physical and psychological impacts, one of which is anxiety. High levels of anxiety in ACS patients can affect the healing process and the patient's quality of life. Family support is seen as one of the important factors that play a role in helping patients overcome anxiety during treatment. This study aims to determine the relationship between family support and anxiety levels in ACS patients at Lavalette Hospital Malang. This study uses an analytical descriptive research design with a cross sectional approach. The study sample was ACS patients treated at Lavalette Hospital Malang with a total of 39 respondents, which were taken using purposive sampling techniques. The research instruments used were family support questionnaires which included emotional, rewarding, instrumental, and informational support, as well as the Hamilton Anxiety Rating Scale (HARS) questionnaire to measure anxiety levels. The results showed that most of the respondents had family support in the high category, namely as many as 20 respondents (51%). Meanwhile, the level of anxiety of respondents showed that almost half did not experience anxiety as many as 17 respondents (44%), a small number experienced moderate anxiety as many as 8 respondents (21%), and some others experienced severe anxiety as many as 14 respondents (36%). It was found that there was a relationship between family support and anxiety levels (p=0.p. 2).Family support has an important role in lowering anxiety levels in ACS patients. Therefore, family involvement in nursing care needs to be increased as part of a holistic care approach to support optimal patient recovery.